2014
DOI: 10.1002/art.38223
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Pain and Disease Symptoms Persist in Juvenile Idiopathic Arthritis Despite Treatment Advances: An Electronic Diary Study

Abstract: Objective To use electronic diaries (e-diaries) to determine whether pain, stiffness, and fatigue continue to be common, disabling symptoms in children with juvenile idiopathic arthritis (JIA) despite the use of aggressive treatments in contemporary medical management. Methods Fifty-nine children with JIA (ages 8–18 years) provided ratings of pain, stiffness, and fatigue intensity and functional limitations using a smartphone e-diary 3 times each day for 1 month. Medication information was collected via pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 39 publications
8
75
1
Order By: Relevance
“…4 Despite recent advances in pharmacotherapy that dramatically improve disease control in children with JIA, other electronic diary (e-diary) findings showed continued daily pain, stiffness, fatigue, and associated functional limitations. 5 We also previously demonstrated that emotion regulation is an important predictor of both pain and function in this sample. 6 Identifying other factors underlying or maintaining both pain and impaired function in JIA is necessary to guide innovations in nonpharmacological treatments.…”
Section: Introductionsupporting
confidence: 55%
“…4 Despite recent advances in pharmacotherapy that dramatically improve disease control in children with JIA, other electronic diary (e-diary) findings showed continued daily pain, stiffness, fatigue, and associated functional limitations. 5 We also previously demonstrated that emotion regulation is an important predictor of both pain and function in this sample. 6 Identifying other factors underlying or maintaining both pain and impaired function in JIA is necessary to guide innovations in nonpharmacological treatments.…”
Section: Introductionsupporting
confidence: 55%
“…This highlights that these constructs are very complex and despite having access to qualitative and quantitative variables, there are still other unidentified factors that likely contribute to pain, quality of life, and physical function. The presence of fatigue and amplified musculoskeletal pain have been reported to influence PROs (30, 31), and this was not systematically recorded in our cohort. Another study suggests that patients place emphasis on being like their peers without a chronic condition and emphasize the psychosocial aspect of living with JIA (32), and these domains were not fully captured by our PROs.…”
Section: Discussionmentioning
confidence: 80%
“…Considerable diversity has evolved over the past decade in how electronic diaries are structured, in how frequently they are completed, and in the health phenomena they are used to study. As evidenced by their use to understand sexual behaviour,4 smoking cessation5 and substance use,6 asthma management7 seizure prediction,8 psychological state and disease symptomatology in old age,9 paediatric arthritis pain,10 and emotional regulation,11 electronic diaries can be a flexible and powerful way to intimately connect to the health experiences of others.…”
mentioning
confidence: 99%